Accidental gods: figures of contingency in the enlightenment fable. Issue 3 (16th March 2018) - Festa, Lynn
ABSTRACT: Drawing on late seventeenth- and early eighteenth-century discussions of fable as myth and apologue, this essay examines the way the form of the fable elicits interpretive practices that enable the reader to recognise the contingency of the mythical figures and fictive forms Enlightenment writers used to make the world intelligible.